StaTips Part I: Choosing statistical test when dealing with differences - Perinetti, Giuseppe (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
When dealing with statistical test hypothesis, one of the most common problems to deal with relates to the difference between oramong groups, treatments or time points. Herein, a short guide is provided to chose the proper statistical test according to the natureof the data and study design.